Methanol and dimethyl ether from renewable hydrogen and carbon dioxide: Alternative fuels production and life-cycle assessment. (15th December 2016) - Matzen, Michael; Demirel, Yaşar
Abstract: In this work we investigate two renewably based alternative fuels; methanol and dimethyl ether. The ultimate feedstocks for production are wind-based electrolytic hydrogen and carbon dioxide captured from an ethanol fermentation process. Dimethyl ether production was modeled in ASPEN Plus using a previously simulated methanol production facility. The facilities use 18.6 metric tons (mt) of H2 and 138.4 mt CO2 per day. Methanol is produced at a rate 96.7 mt/day (99.5 wt%) and dimethyl ether is produced at a rate of 68.5 mt/day (99.6 wt%). A full comparative life-cycle assessment (cradle-to-grave) of both fuels was conducted to investigate their feasibility and sustainability. Renewable methanol and dimethyl ether results were independently compared and this renewable process was also compared to conventional production routes. Results show that production of dimethyl ether impacts the environment more than methanol production. However the combustion of methanol fuel evens out many of the emissions metrics compared to dimethyl ether. The largest environmental impact was found to be related to the fuel production stage for both fuels. Both biofuels were shown to be comparable to biomass-based gasification fuel production routes. Methanol and dimethyl ether from CO2 hydrogenation were shown outperform conventional petroleum based fuels, reducing greenhouse gas emissions 82–86%, minimizing other criteria pollutants (SOx, NOx, etc.) and reducing fossil fuel depletion by 82–91%. The inclusion of environmental impacts in feasibility analyses is of great importance in order to improve sustainable living practices. The results found here highlight the favorable feasibility of renewably produced methanol and dimethyl ether as alternative fuels. Graphical abstract: Highlights: We simulate dimethyl ether production from renewable hydrogen and captured CO2 . A comparative life-cycle assessment is performed for methanol and dimethyl ether. Cradle-to-gate emissions produced for methanol, DME, wind-based H2 and captured CO2 . Cradle-to-grave metrics compared to petroleum and conventionally produced fuels. Renewable routes greatly reduce GHG emissions and lower fossil fuel consumption.